Factors Influencing Solid Waste Management Practices and Challenges in Awi Administrative Zone, Northwestern Ethiopia. - Atnkut, Belsti; Nigussie, Atalaye; Kumera, Bulti; Tsega, Alemu; Tiruneh, Fekadu; Minale, Wondwosson Kibrie; Anemut, Fentanesh; Tazebew, Ewunetu; Terefe, Baye; Fassil, Amare; Gebeyehu, Getaneh; Astatkie, Tess; et al. (BioMed Research International, 2025)
Background: Effective management of solid waste, generated as a result of human activities, is crucial. However, improper solid waste management seriously threatens the environment and public health in developing countries including Ethiopia. Objective: This study is aimed at assessing the status of solid waste management practices and identifying key factors in Awi Administrative Zone, Ethiopia. Methods: A community‐based cross‐sectional study design was used to collect the data and then analyze using descriptive statistics and logistic regression modeling. The survey was conducted in select kebeles (wards) (administrative subdivisions) of Injibara, Dangila, and Chagni towns, using two‐stage sampling techniques. Primary and secondary data sources were utilized. The per capita waste generation rate was calculated based on the total solid waste generated in kilograms per total family size of households per year. Results: The per capita per day solid waste generation rates for Injibara, Dangila, and Chagni were 0.443, 0.456, and 0.487 kg/capita/day, respectively. The composition of household solid waste mainly consisted of biodegradable and nonbiodegradable materials. It was concluded that a significant proportion of household solid waste comprised biodegradable organic matter, which could be efficiently recycled or decomposed through microbial activity. Of the households, 40.6% had access to door‐to‐door solid waste collection service, and 35.9% and 26.2% of the households disposed their solid waste on riverside bridge/drainage lines and roadside/open land, respectively. The regression analysis showed that the head of the household's age, family size, monthly income, solid waste selling practice, solid waste reduction practice, awareness of solid waste disposal rules, frequency of household cleanup campaign participation, and awareness of the impacts of improper solid waste management on the environment and human health were significantly associated with improper solid waste management practices. Conclusion: The study revealed poor performance in solid waste management in the study area, attributed to factors such as inadequate collection system design and schedule, open burning of refuse, substandard condition of the final dumpsite, and lack of community awareness leading to illegal dumping. Recommendations: Based on the findings of the study, we recommend that the town municipality strengthen its door‐to‐door solid waste collection service and distribution of communal bin containers, conduct environmental assessments for better dumpsite selection, and implement a community‐based waste management system to ensure sustainable solutions and continuous education on proper solid waste management practices.